Technical Guidance and Intellectual Property Rights Assistance ‘Sukamulya” Fruit Farmer Group Cirebon, West Java - Muafi Muafi; Siti Nursyamsiah; Fereshti Nurdiana Dihan; Tedy Setiawan Saputra; Ivan Piper (Asian Journal of Community Services, 2023)
This community service aims to provide technical guidance and assistance on intellectual property rights to SMEs who are members of the "SUKA MULYA" Fruit Farmers Group (KT) in Sedong Lor Village, Sedong District, Cirebon, West Java, Indonesia. The service methods used are interactive discussions, outreach and counseling, as well as mentoring.The results of community service activities have been carried out well with indicators; (1) the number of participants and SMEs involved was 100%, (2) the publication of the copyright of the Fruit Farmers Group profile "Suka Mulya" dated 4 September 2023, (3) increased insight regarding copyright and brands and their functions, (4) the composition Fruit Farmers Group "Suka Mulya" profile catalog, (5) gaining knowledge related to economic culture which is expected to improve the regional economy, and (5) increasing insight regarding SME management.